Experimental study and micromechanical interpretation of the poroelastic behaviour and permeability of a tight sandstone. (March 2018) - Wang, Yi; Jeannin, Laurent; Agostini, Franck; Dormieux, Luc; Skoczylas, Frédéric; Portier, Eric
Abstract: This study focuses on the poroelastic behaviour and permeability of tight sandstones, which are characterized by a low porosity, a low gas permeability and a strong sensitivity to in-situ stress. Experimentally the Biot coefficient takes a value close to 1 at low confinement and decreases with increasing confining pressure; the permeability shows an important reduction with increasing confining pressure. This behaviour can be attributed to pore entrapment and to the closure of cracks and joints. Micromechanical models, considering low permeable sandstones as made up of an assemblage of grains with interfaces and pores, reproduce well the observed trends of Biot coefficient and permeability.